Design of Cost Effective Water Treatment Plant in Parala Maharaja Government Engineering Campus - Maharathi, Payal; Swain, Ratnakar (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The dirty water comes from homes due to the domestic uses is what we call as sewage or waste water. Rain water entering drains and industrial waste also appears to fits under this category.Sewage is treated by a variety of methods to make it suitable for its intended use, be it for watering crops or be it for human consumption. Sewage treatment mainly takes place in two main stage i.e. primary and secondary treatment. In arid areas where there is not enough water sewage also undergoes a tertiary treatment to meet the demands of the drinking water supply. During primary treatment the suspended solids are separated from water and BOD (Biochemical oxygen Demands) of the water is reduced. Secondary treatment can be accomplished by a wide variety means, however in our project we will only be concentrating on two of the most commonly used methods i.e. the trickling filter and activated sludge. The activated sludge method uses air and biological floc that is comprised of bacteria and protozoans. Aeration continues for 4-6 hours after which it is stopped and the contents moved into settling tanks. In settling tank flocs settles and removes much of organic matters. The process removes 75-95% of the BOD. In trickling filters 80-85% of the BOD removed. The water is then disinfected mostly by chlorination and released into flowing streams and oceans. If desired, the water can be treated in such a way to make it safe for consumption. This is where tertiary treatment appears. In other words it gives us potable water. It removes phosphorous.
Keywords: Waste water; water treatment